MANTLE-DRIVEN DEFORMATION OF OROGENIC ZONES AND CLUTCH TECTONICS - Tikoff B.; Russo R.; Teyssier C.; Tommasi A. (My University, 2004)
Compatible deformation between the upper crust and upper mantle is documented for a variety of ancient and neotectonic settings, suggesting that these lithospheric layers are coupled. Areas of neotectonic deformation are also characterized by high seismic attenuation. indicating that the uppermost mantle is theologically weak and flowing in these regions. The flow of the mantle, both lithospheric and asthenospheric, potentially drives deformation in continental orogenic zones. Three-dimensional models, controlled by bottom-driven mantle flow, are proposed for obliquely convergent, transcurrent and obliquely divergent plate margins. Our analysis indicates that the absolute, and not Just relative, plate motions play a critical role in the orogenic cycle.